Digital Preservation: Putting It to Work - Traczyk, Tomasz; Ogryczak, Włodzimierz; Pałka, Piotr; Śliwiński, Tomasz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses the process of maintaining digital objects through time to ensure continued access, an aspect that has become a crucial issue in recent years. It oﬀers a concise yet comprehensive discussion of key concepts and requirements for long-term digital preservation, and presents a pioneering framework for digital repositories that enables the long-term archiving and metadata management for large volumes of digital resources based on a system that has already been completely designed and launched. In the framework, the reliability of information readouts is ensured by the repository with two-level data recording replication and monitoring mechanisms in the repository management system (RMS) and the ﬁle systems, and by the RMS's distributed nature. The advanced RMS allows operations on the archival storage to be scheduled, while also taking into account low energy consumption requirements. After presenting the framework in detail, the book assesses and demonstrates the approach's viability in terms of delivering accessibility, authenticity and usability. As such, the book offers a valuable resource for information technology (IT) researchers and practitioners, as well as archivists and librarians.
Chapter 1: Requirements for Digital Preservation -- Chapter 2: Metadata in Long-term Digital Preservation -- Chapter 3: The CREDO Project -- Chapter 4: CREDO Repository Architecture -- Chapter 5: Information Processing in CREDO Long-term Archive -- Chapter 6: Metadata in CREDO Long-term Archive -- Chapter 7: Persistence Management in Long-term Digital Archive -- Chapter 8: Power Efﬁciency and Scheduling Access to the Archive -- Chapter 9: Information Management in Federated Digital Archives.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence